Consequences of Talak, Khulu' and Marriage Fasakh Based on a Compilation of Islamic Law in Indonesia - SAPUTRA, Deris Arista (PT. Keberlanjutan Strategis Indonesia, 2024)
Purpose:This study examines the effectiveness of the Compilation of Islamic Law (KHI) in handling divorce cases through talak, khulu’, and fasakh in Indonesia. This study aims to understand the significant role of KHI in providing justice for couples experiencing marital conflict.Methodology:Using library methods, data were collected from various literature sources and religious court decisions related to talak, khulu’, and fasakh. This study uses a library method, a systematic approach to reviewing and analyzing data from various literatures. This library research type studies theory, concepts, and regulations relevant to divorce cases through talak, khulu', and fasakh decisions.Findings:The results show that KHI functions not only as a formal rule but also as an instrument of protection for women and children and supports post-divorce welfare. These findings confirm that KHI has important flexibility relevant to the country's social conditions and can be used as a model for ethically and contextually responsive Islamic family law.Implication:This research provides an essential contribution to the development of science, both theoretically and practically. Theoretically, this research strengthens the understanding of the adaptation of Islamic law in the modern context, mainly how the KHI as a derivative of Islamic law can be applied effectively in a pluralistic society. Practically, this research enriches the study of Islamic family law in Indonesia by providing empirical data showing that the mechanisms of talak, khulu', and fasakh can be implemented formally and ethically.